2003
DOI: 10.1002/ptr.1198
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of fenugreek (Trigonella foenum graecum) seeds in experimental ethanol toxicity

Abstract: The study investigates the effect of aqueous extract of fenugreek seeds (Trigonella foenum graecum) on lipid peroxidation and antioxidant status in experimental ethanol toxicity in rats. The ability of the seed extract to prevent iron-induced lipid peroxidation in vitro was also investigated. Ethanol feeding for 60 days resulted in significant increases in the activities of serum aspartate transaminase, alanine transaminase and alkaline phosphatase. The levels of serum lipid hydroperoxides and thiobarbituric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 22 publications
5
78
0
Order By: Relevance
“…The seed oil of fenugreek was selected for this study, since fenugreek is commonly used as a spice in food preparations due to the strong flavour and aroma. The seeds are reported to have restorative and nutritive properties (Khosla et al, 1995), such as anti diabetic activity (Sharma et al, 1990), hepatoprotective activity (Thirunavukkarasu et al, 2003;Kaviarasan and Anuradha, 2007), and antioxidant properties against experimental cataract (Gupta et al, 2010). In recent research, fenugreek seeds were experimentally shown to protect against breast (Amin et al, 2005) and colon cancers (Raju et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seed oil of fenugreek was selected for this study, since fenugreek is commonly used as a spice in food preparations due to the strong flavour and aroma. The seeds are reported to have restorative and nutritive properties (Khosla et al, 1995), such as anti diabetic activity (Sharma et al, 1990), hepatoprotective activity (Thirunavukkarasu et al, 2003;Kaviarasan and Anuradha, 2007), and antioxidant properties against experimental cataract (Gupta et al, 2010). In recent research, fenugreek seeds were experimentally shown to protect against breast (Amin et al, 2005) and colon cancers (Raju et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Its utility has also been proved experimentally in diabetic humans (Sharma et al, 1990). Hepatoprotective properties of fenugreek seeds in experimental models (Thirunavukkarasu et al, 2003;Kaviarasan and Anuradha, 2007) and antioxidant properties of fenugreek seeds against experimental cataract (Gupta et al, 2010) were also reported. In recent research, fenugreek seeds were experimentally shown to protect against breast (Amin et al, 2005) and colon cancers (Raju et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…In a word, the FPEt increased the activities of antioxidant enzymes and enhanced the antioxidant properties, which could be the potential mechanisms of action in chronic alcohol-fed mice. The protective effect was possibly due to the bioactive antioxidants in fenugreek seeds such as polyphenols [57][58][59]. As a result, Trigonela foenum-graecum might have a positive influence on suppressing the abnormalities induced by alcohol in chronic alcohol liver diseases through its antioxidant properties.…”
Section: Trigonela Foenum-graecummentioning
confidence: 99%
“…Several mechanisms were postulated to be involved in ethanol neurodegeneration, some of them also being involved in MDMA-induced neuronal damage. Among the most relevant are excessive glutamatergic activity (Tsai et al 1995), increased intracellular calcium (Lovinger 1993) and an oxidative stress process (Bondy et al 1996;Crews et al 2004) mediated by a rise in oxygen and nitrogen-derived reactive species (Lancaster 1992;Reddy et al 1999;Huang et al 2002;Dahchour et al 2005), a reduction in the activity of the main antioxidant enzymes and an increase in the degree of lipid peroxidation (Somani et al 1996;Fadda and Rossetti 1998;Reddy et al 1999;Agar et al 2003;Thirunavukkarasu et al 2003).…”
mentioning
confidence: 99%